(untitled) (Journal of the College of Basic Education, 2023)
The subject of the Mutasarrifate of Mount Lebanon (1861-1918) is considered one of the topics that deserves study because the mountain region enjoyed semi-independent political activity from the Ottoman Empire in its seven provinces (Koura, Batroun, Keserwan, Metn, Zahle, Chouf, and Jezzine). As the Ottoman state did not have the right to interfere in its internal affairs except after the approval of the European countries, as was decided in the Istanbul Conference on the ninth of June 1861, which counted these seven provinces that constitute Mount Lebanon as an autonomous region enjoying autonomy. Outside Mount Lebanon, it shall be agreed upon in coordination with representatives of European countries (France, Britain, Russia, Prussia, and Austria). This particularity of Mount Lebanon came as a result of the outbreak of civil wars between the inhabitants of these provinces in the years 1841, 1845, and the last of which was in 1860, which was more deadly for the Lebanese. The second party is the Maronite Christians. Following the intensification of the struggle between the two communities to control the government, the aforementioned European countries intervened in the affairs of Mount Lebanon as protectors of the Christian subjects in the Ottoman Empire. Due to the religious specificity of the residents of Mount Lebanon, being a mixture of several sects and sects, the constitution of 1861 was legislated, which consisted of seventeen articles and an appendix that was amended in 1864, and six other articles were added to it in 1912. After the outbreak of World War I in 1914 and the entry of the Ottoman Empire into the war against France and Britain, the Ottoman government worked to end the Mutasarrifiyah system in 1918 and rule it directly